2016
DOI: 10.1017/ice.2016.35
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Room Location on UV-C Irradiance and UV-C Dosage and Antimicrobial Effect Delivered by a Mobile UV-C Light Device

Abstract: OBJECTIVETo evaluate ultraviolet C (UV-C) irradiance, UV-C dosage, and antimicrobial effect achieved by a mobile continuous UV-C device.DESIGNProspective observational study.METHODSWe used 6 UV light sensors to determine UV-C irradiance (W/cm2) and UV-C dosage (µWsec/cm2) at various distances from and orientations relative to the UV-C device during 5-minute and 15-minute cycles in an ICU room and a surgical ward room. In both rooms, stainless-steel disks inoculated with methicillin-resistant Staphylococcus aur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 14 publications
1
45
0
Order By: Relevance
“…Previous studies have demonstrated that exposure times of 10 minutes or longer may provide sufficient UV-C dosing to reduce C. difficile spores by 2 logs or more. 18,[20][21] Our study has some limitations. We assessed contamination of the radiology department with a single point-prevalence culture survey.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have demonstrated that exposure times of 10 minutes or longer may provide sufficient UV-C dosing to reduce C. difficile spores by 2 logs or more. 18,[20][21] Our study has some limitations. We assessed contamination of the radiology department with a single point-prevalence culture survey.…”
Section: Discussionmentioning
confidence: 94%
“…Our findings are consistent with 3 recent reports in demonstrating that measurements of irradiance may be useful in understanding decontamination performance of different devices. [20][21][22] If a radiometer is available, measurement of irradiance can be completed quickly and easily. Alternatively, commercial test cards can provide a simple and easy-to-use colorimetric assessment of UV output.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 A multicenter, randomized controlled trial of a mobile UV device and other smaller studies have shown that UV devices can decrease surface contamination and reduce healthcare-associated infections (HAIs); effect size is dependent upon the type of microorganisms and the type of disinfectant used in the comparator groups. [8][9][10][11][12][13][14] A recent systematic review and meta-analysis of no-touch disinfection technologies evaluated 13 studies that used UV devices. 15 When the results of the studies were pooled, statistically significant reductions in the rates of infections caused by Clostridioides difficile.…”
Section: Introductionmentioning
confidence: 99%
“…7,16 Determining the effectiveness of devices is complicated by lack of standard methods for testing UV-C devices, limited published data on the doses of UV delivered to various surfaces in patient rooms, and conflicting data on the UV dose (fluence) necessary to achieve desired reductions of various healthcare pathogens, including C. difficile. 12,[17][18][19][20][21][22][23][24] Healthcare personnel would benefit from a basic understanding of the characteristics of UV-C, the availability of more evidence on the UV-C doses delivered to surfaces in patient rooms, and knowledge of the UV-C doses required to reduce specific healthcare pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…8 Our log 10 reductions of 6 or higher for MRSA are larger than those of prior studies, most likely due to differences in inoculum size. 9,10 Our study has several limitations. We sampled Formica sheets instead of sampling directly from clinical surfaces.…”
Section: Discussionmentioning
confidence: 94%